A business in baking - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Cereal processing offers good potential for anyone wanting to set up a small or medium-scale business, either for Setting up and Running a Small Flour Mill or Bakeryprimary processing converting grain to flour or secondary processing, which ...